Adverse cardiac events in out‐patients initiating clozapine treatment: a nationwide register‐based study. (24th October 2017) - Rohde, C.; Polcwiartek, C.; Kragholm, K.; Ebdrup, B. H.; Siskind, D.; Nielsen, J.
Abstract : Objective: Using national Danish registers, we estimated rates of clozapine‐associated cardiac adverse events. Rates of undiagnosed myocarditis were estimated by exploring causes of death after clozapine initiation. Method: Through nationwide health registers, we identified all out‐patients initiating antipsychotic treatment (January 1, 1996–January 1, 2015). Rates of clozapine‐associated myocarditis and pericarditis within 2 months from clozapine initiation and rates of cardiomyopathy within 1–2 years from clozapine initiation were compared to rates for other antipsychotics. Mortality within 2 months from clozapine initiation was extracted. Results: Three thousand two hundred and sixty‐two patients of a total 7932 patients initiated clozapine as out‐patients (41.12%). One patient (0.03%) developed myocarditis, and no patients developed pericarditis within 2 months from clozapine initiation. Two (0.06%) and four patients (0.12%) developed cardiomyopathy within 1 and 2 years respectively. Rates were similar for other antipsychotics. Twenty‐six patients died within 2 months from clozapine initiation. Pneumonia (23.08%) and stroke (11.54%) were the main causes of death. We estimated the maximum rate of clozapine‐associated fatal myocarditis to 0.28%. Conclusion: Cardiac adverse effects in Danish out‐patients initiating clozapine treatment are extremely rare and these rates appear to be comparable to those observed for other antipsychotic drugs.